Моделювання впливу інвестицій у смарт-технології на розвиток переробної промисловості на прикладі Німеччини - Охтень, О.О. (Економіка промисловості, 2025)
На прикладі Німеччини проаналізовано вплив інвестицій у смарт-технології на розвиток переробної промисловості з використанням виробничої функції, яка додатково враховує чинник цифровізації у формі нематеріальних активів, які в обраній галузі складаються майже виключно з програмного забезпечення, баз даних, а також науково-дослідних та дослідно-конструкторських робіт. Посилення впливу цього чинника дає більший приріст доданої вартості, ніж зростання обсягу капіталу, тому стимулювання розвитку смарт-промисловості має здійснюватися шляхом спрямування інвестицій у проєкти, які сприяють цифровізації. Встановлено, що поточна структура інвестицій у переробну промисловість України демонструє більш ніж десятикратне відставання від Німеччини за показником співвідношення інвестицій у цифровізацію до інвестицій у машини та обладнання. One of the main trends observed in the manufacturing sector at the current stage of economic development is the introduction of smart technologies, i.e. innovative solutions that integrate sensors, automation, artificial intelligence and the Internet of Things, to increase the efficiency, accuracy and flexibility of production processes. Leading countries in this area, in particular the USA, China and EU countries, are implementing various measures to stimulate the development of smart industry, including budgetary and fiscal one, with a total cost of tens of billions of dollars per year, however, less economically developed countries need to choose the most effective directions of resource allocation, which requires assessing the impact of investments on the performance of the manufacturing sector. The article is devoted to the analysis of the impact of investments in smart technologies on the development of the manufacturing industry using the example of Germany, which is the largest economy in the Eurozone and one of the leaders in the development of smart industry. For this purpose, a production function model was built that takes into account not only traditional production factors, such as labor and capital, but also the factor of digitalization. The model is based on a multiplicative production function (which includes standard factors such as capital in the form of the cost of machinery and equipment, as well labor in the form of total wages in the industry), modified by adding the cost of intellectual property as a separate factor (which in the processing industry consists of the cost of software, databases and scientific and technical research). Modeling on the example of Germany showed that the growth of this smart factor gives a greater increase in added value than the growth of the capital factor, which indicates that stimulating the development of smart industry should be carried out in the form of directing investments into projects of a specific profile: which increase the cost of machinery and equipment, as well as the digitalization factor. Moreover, with the account technical feasibility and economic feasibility, the share of investments in the digitalization factor should be higher than the share of capital investments. A comparison of the structure of investments in production factors in Ukraine and Germany was carried out, which showed that the current structure of investments in the manufacturing industry in Ukraine does not meet the criteria for the development of smart industry due to Ukraine's more than 10-fold lag in terms of the ratio of investments in the digitalization factor to investments in machinery and equipment. Recommendations were also provided to improve the structure of statistical information by including additional indicators that take into account the features of smart industry.